Latin American and Caribbean integration and cooperation organizations activities and spheres of action (SELA CaracasVE, 1994)
Describes the areas and the activities which the secretariats of the economic integration organizations cover. Gives a summary of the activities of organizations and mechanisms dedicated to regional cooperation. Identifies Latin American sub-regional associations, entities and programmes, both public and private, as well as United Nations programmes which operate in the region.
DC